Bioinspired coating of TiO2 nanoparticles with antimicrobial polymers by Cu(0)-LRP: grafting to vs. grafting from. Issue 42 (20th October 2017) - Guo, Shutong; Zhang, Qiang; Wang, Donghao; Wang, Lu; Lin, Fang; Wilson, Paul; Haddleton, David M.
Abstract : Titanium dioxide nanoparticles coated with non-leachable biocides were prepared by Cu(0)-LRP of tertiary-amine-containing monomers via "grafting to" and "grafting from" strategies. Abstract : In this study, titanium dioxide (TiO2 ) nanoparticles coated with non-leachable biocides were prepared by chemically attaching tertiary-amine-containing polymers to the surface of TiO2 . Copper(0)-mediated living radical polymerization (Cu(0)-LRP) was utilized to fabricate the effective antibacterial surfaces via both "grafting to" and "grafting from" strategies. The Cu(0)-LRP of 2-(dimethylamino)ethyl methacrylate (DMAEMA) and 2-(diethylamino)ethyl methacrylate (DEAEMA) was first performed directly from an unprotected dopamine-functionalized initiator using either a commercial copper wire or in situ generated copper powders from the disproportionation of CuBr/Me6 TREN as the activators. The synthesized dopamine-terminal polymers were grafted on the surface of TiO2 via strong catechol bonding to yield an environmental-responsive surface. Subsequently, the tertiary amine polymers were directly grafted from the TiO2 nanoparticles via surface initiated Cu(0)-LRP in DMSO or aqueous solutions, which showed a higher grafting density. The obtained TiO2 @polymer hybrid nanocomposites showed good dispersion stability in water and efficient recovery could be achieved due to the self-flocculation effect. The degradation of rhodamine B under the irradiation of simulated sunlight proved the maintenance of photocatalytic ability after the surface modification of TiO2 . The antibacterial activity of the tertiary amine polymer-coated nanocomposites before and after quaternization was tested against Escherichia coli ( E. coli ), during which the unmodified tertiary amine polymer surprisingly inhibited the growth of E. coli and the quaternized polymer showed almost 100% killing efficiency.